Oblicz 33% liczby a, gdy a=(-2)potęga 3 [-2/3 *(3potęga2/pierwiastek64) -4/3*(-3/8)]
=-8*[-2/3*(9/8)+1/2]=
=-8*[-3/4+ 2/4 ]=
=-8*[-1/4]=
=2
33% z liczby a:
33% * 2 = 33/100*2=66/100=0,66
a=(-2)³* [-2/3*(3²/√64)-4/3*(-3/8)]
a=-8* [ -2/3 * 9/8+3/6 ]
a=-8*(-3/4+1/2)
a=-8*(-9/12+6/12)
a=-8*(-3/12)
a=6/3
a=2
33%=33:100=0,33
0,33*2=0,66
Odp: 33% liczby 2 wynosi 0,66
" Life is not a problem to be solved but a reality to be experienced! "
© Copyright 2013 - 2025 KUDO.TIPS - All rights reserved.
=-8*[-2/3*(9/8)+1/2]=
=-8*[-3/4+ 2/4 ]=
=-8*[-1/4]=
=2
33% z liczby a:
33% * 2 = 33/100*2=66/100=0,66
a=(-2)³* [-2/3*(3²/√64)-4/3*(-3/8)]
a=-8* [ -2/3 * 9/8+3/6 ]
a=-8*(-3/4+1/2)
a=-8*(-9/12+6/12)
a=-8*(-3/12)
a=6/3
a=2
33%=33:100=0,33
0,33*2=0,66
Odp: 33% liczby 2 wynosi 0,66